ADVANCING DIGITAL MARKETING IN MOLDOVA: AN ANALYSIS BASED ON A SOCIOLOGICAL SURVEY OF ENTREPRENEURS - Gagauz, Valerii; Gagauz, Olga (Economy and Sociology, 2023)
The article presents the results of the study on the implementation of digital marketing in Moldovan enterprises. Based on a sociological study conducted by the author in May-June 2023 among entrepreneurs (N=131), the level of digital marketing usage, current trends, awareness of digital marketing technologies and tools, as well as the difficulties encountered by entrepreneurs in using digital marketing tools, are identified. The data has been processed using multiple correspondence analysis (MCA) and Hierarchical Clustering on Principle Components (HCPC) in the programming language R. The research is descriptive in nature, as it aims to gather empirical information that provides a comprehensive understanding of the phenomenon under investigation and its structural elements. Four clusters, each comprising enterprises of different sizes, were identified: 1) enterprises less advanced in digital marketing, 2) enterprises with complex marketing strategies but limited resources, 3) enterprises that combine traditional and digital marketing methods, 4) the most advanced enterprises in digital marketing. Marketing on social media holds a prominent position in the marketing activities of enterprises regardless of their size. SMEs face certain challenges in marketing activities overall and in the use of digital marketing tools, in particular. Previous research on this topic is quite limited, and this current study is unique in that it considers the issue in the context of SMEs and Central and Eastern European countries. We show that SMEs, along with large companies, can have complex marketing strategies and successfully use modern digital marketing tools.